Differentiation of Tracheary Elements in Sugarcane Suspension Cells Involves Changes in Secondary Wall Deposition and Extensive Transcriptional Reprogramming - Simões, Marcella Siqueira; Ferreira, Sávio Siqueira; Grandis, Adriana; Rencoret, Jorge; Persson, Staffan; Floh, Eny Iochevet Segal; Ferraz, André; del Río, José C.; Buckeridge, Marcos Silveira; Cesarino, Igor (Frontiers in Plant Science, 2020)
Plant lignocellulosic biomass, mostly composed of polysaccharide-rich secondary cell walls (SCWs), provides fermentable sugars that may be used to produce biofuels and biomaterials. However, the complex chemical composition and physical structure of SCWs hinder efficient processing of plant biomass. Understanding the molecular mechanisms underlying SCW deposition is, thus, essential to optimize bioenergy feedstocks. Here, we establish a xylogenic culture as a model system to study SCW deposition in sugarcane; the first of its kind in a C4 grass species. We used auxin and brassinolide to differentiate sugarcane suspension cells into tracheary elements, which showed metaxylem-like reticulate or pitted SCW patterning. The differentiation led to increased lignin levels, mainly caused by S-lignin units, and a rise in p-coumarate, leading to increased p-coumarate:ferulate ratios. RNAseq analysis revealed massive transcriptional reprogramming during differentiation, with upregulation of genes associated with cell wall biogenesis and phenylpropanoid metabolism and downregulation of genes related to cell division and primary metabolism. To better understand the differentiation process, we constructed regulatory networks of transcription factors and SCW-related genes based on co-expression analyses. Accordingly, we found multiple regulatory modules that may underpin SCW deposition in sugarcane. Our results provide important insights and resources to identify biotechnological strategies for sugarcane biomass optimization.